Maintenance policy selection of N-component repairable system using genetic algorithm - Srivastava, Nishit Kumar; Kuila, Pratyay; Chatterjee, Namrata; Subramani, A K; Jan, N Akbar (Serbian Journal of Management, 2022)
A typical manufacturing system consists of a large number of repairable components/ machines which age with time and require maintenance. This paper proposes a novel maintenance policy selection method using genetic algorithm. Where, maintenance problem is formulated for n- component repairable system to minimize the total maintenance cost. The various maintenance policies and repairable components are represented in the form of chromosomes, initially various chromosomes are randomly generated which are then assessed and selected using fitness value and then crossover and mutation function is performed to obtain a better chromosome. Several iterations are performed till the desired results is achieved. The proposed algorithm is further explained and validated through an illustrative example.
Keywords: Artificial Intelligence (AI); corrective maintenance; preventive maintenance; redictive maintenance; Genetic Algorithm (GA)